Relationship between the Coloration Mechanism and Gemological Properties of Purple Scapolite - Yinghua Rao; Qingfeng Guo; Sixue Zhang; Libing Liao (Crystals, 2023)
Purple scapolite is a precious gemstone. In this paper, we compared the crystal structure and spectral characteristics of purple scapolite before and after heat treatment with conventional gemological tests, EPMA, XRF, LA-ICP-MS, infrared spectroscopy, Raman spectroscopy, UV–vis spectrophotometer, EPR, and other tests. The XRD results showed that the structure of purple scapolite fits perfectly with that of marialite. Compositional analyses indicate that purple scapolite has an average Me value of 16.85 and belongs to the subspecies marialite, and thus its specific gravity and refractive index are low. The absorption peak at 1045 cm−1 in the infrared spectra has a direct relationship with the Me value, which is blue-shifted with increasing Me value. After heating at 400 °C for 2 h, the purple scapolite changed to colorless, and no phase transformation or significant structural changes occurred during this process. But this process is accompanied by the disappearance of the signal at g = 2.011 in the EPR spectra, which indicates the presence of oxygen hole centers, thus proving that the color of purple scapolite is caused by oxygen hole centers rather than Fe3+. The chlorine in the marialite structure occupies the structural center, which provides for the appearance of oxygen hole centers, and thus purple scapolite always has a high marialite content. This further leads to the refractive index and specific gravity always being lower. That is a new explanation for the relationship between scapolite coloration mechanism, specific gravity, and refractive index.